A New Approach to Challenges of Venture Capital in Financing the Industrial Clusters through Cooperative Models and Venture Funds in Iran - Nezhad, Abdol Majid Saadat; Sohrabi, Tahmoures; Shadnoosh, Nasrollah; Eshlaghy, Abbas Toloie (International Journal of Economics and Financial Issues, 2017)
While science and technology parks and towns and development centres have been established before 2002 in Iran and their number have been continually increased, there has been only a seminar presented by Mr Abdeh Tabrizi, the late Secretary General of Tehran Securities and Exchange Organization, in Bank Sepah, 2001, about venture capital in the country. Gradually, venture capital have been presented as a new mechanism for financing to entrepreneurs and a bill has been represented to cabinet by Management and Planning Organization to define an annual definite budgetary in a general manner. The industry of venture capital has been under attention by many organizations and science centres during recent years. The Institute of Elites’ technological development, on behalf of Centre for Innovation and Technology Cooperation (CITC), Presidency of Islamic Republic of Iran, Management and Planning Organization of Iran, Industrial Development and Renovation Organization of Iran, Centre for New Industries of Iran, Youth occupation cooperation organization or Iran, Bank Keshavarzi, Tadbir Investment Company, Iran National Investment Company, Farda Development Institute, University of Tehran, Sharif University of Technology, Imam Sadegh University, and other financial organizations and institutes have been the centres that represented their research results in the First Conference of Venture Capital, held by Jahad Daneshgahi, University of Tehran. Sanaray Company, a consortium consists of active Iranian companies in the field of information technology, have been represented some examples of successful business plans and ideas in Iran to Enjazat Fund during last two years, in cooperation with Islamic Development Bank. Based on the represented plans, this fund has been responsible for investing up to 50 million dollars in Middle East and North of Africa. Currently, Mr Saffari is the Iranian consultant of the fund. Keywords: Industrial Clusters; Export–Oriented Clusters; Venture Funds; SPV; PPP; Venture Capital; Cooperative Models JEL Classifications: C38, G24, L24